PERANCANGAN SISTEM INFORMASI BERBASIS WEB FRONT END (STUDI KASUS WARUNG NASI GORENG ABAH KARIM PALMERAH BARAT) - Malik Miftakhul Khaq; Tri Hidayati (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Fried rice stalls are a business that is in great demand by the middle and lower class, because in general many people understand and are familiar with fried rice sellers, Warung Nasi Goreng "Abah Karim" which was established in 2012 is one of the fried rice stalls located in Palmerah Barat, West Jakarta is open from 17.00 to 24.00 WIB. Warung Nasi Goreng Abah Karim until now there is no website available for promotional media and information so that not many people know it, because they do not yet have an information system in the form of a website. The purpose of this research is to create a website information system to provide better service. The information system design was created using the Waterfall method and structured analysis modeling. This system was created using the programming language commonly used in website creation, namely the PHP programming language and MySQL database. The results of this study are that the website system can provide convenience for customers in receiving information and promotions interactively and effectively so that later it will be able to facilitate the selling process at the Abah Karim fried rice shop